Effects of N/Ne impurity seeding on the divertor asymmetry in HL-2A tokamak - Qingyi Tan; Haoran Ye; Xueyu Gong; Yijun Zhong; Qianhong Huang; Zhe Wang; Chengzhi Cao; Zhanhui Wang; Cailong Fu; Min Xu; Tao Yang (Nuclear Fusion)
Divertor asymmetry is a major challenge in achieving high-power, long-pulse discharges in future fusion reactors. Impurity seeding is the most common method for achieving divertor detachment in fusion devices. In this study, the SOLPS-ITER code is used to investigate the impact mechanisms of nitrogen (N) and neon (Ne) impurity seeding on the asymmetry between the inner and outer divertor in HL-2A under the attached and detached divertor conditions. Results indicate that N and Ne impurity seeding can increase asymmetry of energy and particle flux between the inner and outer targets. The trend in the energy flux ratio between the inner and outer targets is consistent with that of the particle flux ratio. Research indicates that under the attached divertor condition, the increase in energy flux asymmetry due to impurity seeding is primarily influenced by the electron temperatures between the inner and outer targets. However, when under the detached divertor condition, the increased asymmetry in energy and particle flux is primarily attributed to impurity seeding, which narrows the ion source generation in the inner divertor while broadening the ion sink region compared to the outer divertor.